AI-Driven Disruption in Retail and Education Featuring Chegg, Stack Overflow, RWS, and Duolingo - Ramayu, I Made Satrya; Darmawan, Andreas James; Heptariza, Anita; Sihwinarti, Dwi (Indonesian Business Review, 2025)
The artificial intelligence (AI) revolution has brought significant disruption to the digital business industry, including the online retail education services sector. On the one hand, the application of AI in the corporate environment is often followed by a reduction in human labor. On the other hand, the use of AI by consumers challenges the existence of digital service companies, especially those engaged in online education. This research analyzes how business sustainability in this sector is not enough to adapt to AI, but needs to adopt AI strategically to create added value and stronger competitiveness. Through case studies on Chegg, Stack Overflow, RWS, and Duolingo; this research evaluates the impact of AI on business models, effective adaptation strategies, and growth opportunities amid the threat of disruption. The results show that companies that are able to integrate AI as part of product and service innovation are not only able to survive, but also have the potential to expand market share and create new trends in the online education industry.